If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6y = -6x + 34 Reorder the terms: 3x + -6y = 34 + -6x Solving 3x + -6y = 34 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 3x + 6x + -6y = 34 + -6x + 6x Combine like terms: 3x + 6x = 9x 9x + -6y = 34 + -6x + 6x Combine like terms: -6x + 6x = 0 9x + -6y = 34 + 0 9x + -6y = 34 Add '6y' to each side of the equation. 9x + -6y + 6y = 34 + 6y Combine like terms: -6y + 6y = 0 9x + 0 = 34 + 6y 9x = 34 + 6y Divide each side by '9'. x = 3.777777778 + 0.6666666667y Simplifying x = 3.777777778 + 0.6666666667y
| 4.7x-5.48=11.44 | | (K+2)(6k-7)=0 | | x=ax+1a+bx-2b | | 12-3x+9x=14+6x | | 5x^2+4xy+2y^2=6 | | 3d-274d+10c=120 | | 2x=17x+15 | | 11x+61=Ax+Bx+5A+8B | | 6-2y=10-8y+6y | | x-22x+2y=4 | | 11x+61=Ax+Bx+5A+8A | | (x-2)2x+2y=4 | | (-8)-14= | | 6g-4h=-2g+28 | | 2m-7n-4m+9n= | | 5p+8m=-10p+3 | | 4x-8y=2x+10 | | 8-n(2)=20 | | 81-x^4=0 | | 5N^3+2N^2+15N=0 | | 10+x-(2-3x)=4 | | 1080=26x+95 | | 2t+1=-1 | | 26x+95=1080 | | 7(x+1)+6=4x+3(4+x) | | x+8=-1 | | X^2-(32+2i)x+62i=0 | | 2y+5y=35 | | 7X+3=3X-7 | | 2b-3d-3b+6d= | | -5+4x=7 | | 7=6n-5 |